2014
DOI: 10.1007/s00402-014-2072-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical fit of seven different palmar distal radius plates

Abstract: Although there was no complete congruency between the plates and the radial cortex, all distal palmar radius plates investigated in this study presented a reasonable anatomical shape. The Synthes VA-LCP distal two-column-radius plate palmar showed the best anatomical fit. A low profile and optimized anatomical precontouring minimizes irritation of the surrounding soft tissues and should be considered with plate design and implant choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Use of the palmar locking plate after open reduction is the most common surgical treatment for unstable distal radius fracture [1,12,13]. Although palmar locking plate fixation is a good treatment option for most distal radius fractures, the palmar locking plate has some complications and limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of the palmar locking plate after open reduction is the most common surgical treatment for unstable distal radius fracture [1,12,13]. Although palmar locking plate fixation is a good treatment option for most distal radius fractures, the palmar locking plate has some complications and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although palmar locking plate fixation is a good treatment option for most distal radius fractures, the palmar locking plate has some complications and limitations. The overall complication rate ranges from 8 to 39 % and can include complex regional pain syndrome type I and damage to both the flexor and extensor tendons [12][13][14]. The palmar locking plate has limitations when used to treat several clinical conditions including AO/OTA C3 type fracture and small volar rim fracture with comminution.…”
Section: Discussionmentioning
confidence: 99%
“…These assessed gross measurements (distal sagittal and axial width) [8–10, 25] or the cross-sectional anatomy of the distal radius [11, 26, 27]. Some studies indicated to assess the 3D anatomy of the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…No sample size calculation could be conducted due to missing preliminary data. Previous studies investigating the volar cortical angle of the distal radius included 74 ± 23 patients on average [911, 1719]. Therefore, we aimed at a study population of 90 radii (mean + 1SD) and a gender ratio of 50% female.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation